First record of Myrrha octodecimguttata (Coleoptera: Coccinellidae) and Epuraea ocularis (Coleoptera: Nitidulidae) from Israel - Rittner, Oz; Nir, Assaf (Zootaxa, 2013)
Myrrha octodecimguttata (Linnaeus, 1758) and Epuraea ocularis Fairmaire, 1849 are recorded from Israel for the first time, both species collected in Shoham Forest.